Improving Students’ Creativity through Development of Teaching Material Lampung Local Wisdom Search, Draw, and Make-Based (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
The objective of the study was to realize of Lampung local wisdom teaching materials Search, Draw, and Make-based that were feasible and effective to use to improve the creativity of students. The study was conducted at IV.A SDN 2 Gedong Tataan totaling 10 students. The study was a Research and Development (R&D) carried out by referring to the Borg & Gall design model with a simplification of 8 steps. The results of this study were in accordance with the results of the feasibility test for the development of human resource-based Lampung local wisdom teaching materials using material experts reaching a percentage of 78%, media experts reaching a percentage of 76%, linguists reaching a percentage of 79% and the results of effectiveness were proven by pre-test results 64.5% and post test 86.5%. This indicates that the effect of using Lampung local wisdom teaching materials Search, Draw, and Make-based is proven to improve the creativity of students in the aspects of fluency, flexibility, originality, and elaboration.